Oral manipulation, activity level and pen hygiene of growing pigs provided with straw by a foraging tower - Söderqvist, Matilda (SLU/Dept. of Animal Environment and Health (until 231231), 2016)
In nature pigs spend a large part of their active time foraging, a behaviour in which their snout plays a big role. In an intensive system pigs have an extremely limited possibily to perform natural behaviour such as foraging. The floors in intensive modern systems are often bare and the pigs are provided with a restricted amount of bedding material. Inability to perform natural behaviours may lead to stress and development of stereotypies and is an indicator that the animal has trouble handling the environment. The animal can for instance be less active and spend a lot of time motionless. The objective of this study was to determine whether environmental enrichment in the form of a straw dispenser has any effect on the level of exploratory behaviour, activity and manipulation of penmates. The pen hygiene and amount of leftover straw were scored during the experiment to examine the effect a foraging tower had on hygiene and straw consumption. Enrichment was provided with a substrate dispenser (foraging tower) from which the pigs could pull straw through the bottom of the tube. An experiment was performed in three batches during a total of three weeks on growing pigs (< 35 kg) housed for commercial use. Nine groups per batch were exposed to one of three treatments: straw on floor (C); straw on floor and empty foraging tower (E); and straw on floor and straw in foraging tower (F). In each group, pig behaviour was observed through direct scan sampling of all pigs every 4 minutes during 2 hours on one day. A scan of all pigs in each pen was performed two times a day (8h00-9h00; 11h00-12h00). The observed exploration had a total mean percentage of 26,3% (E), 26,4% (F) and 25,9% (C) during both observation sessions. Results showed a significant difference in activity level, exploration and manipulation of penmates, especially between group F and C. The activity level amongst all pigs were overall lower during the second (11h00-12h00) observation compared to the first. As the straw was distributed at 9h30 the growing pigs may have, by the second observation, fulfilled most of their rooting needs. Oral manipulation of penmates tended to occur significantly less often in group F compared to the other groups (E and C). The pen hygiene was not affected much by the different treatments which means that this kind of environmental enrichment is relatively compatible with the manure handling system used in the modern housing systems. The mean average of straw consumption in group F was 449 g/day compared to 353 g given on the floor in group E and C. Overall the F pigs had a higher amount of clean straw left on the first observation compared to the other groups. Since there were no differences in behaviour between group E and C, the results suggest that the foraging tower per se did not stimulate activity or exploration in the pens. The stimuli should therefore have been the straw provided in the dispensers.